Method Improving for Isolation and Characterization of Allergy-Inducing Polymer Impurities in Cefotaxime Sodium Medicines Available From Pharmaceutical Industry - Fu, Yanan; Li, Jin; Feng, Fang; Yin, Lihui (Frontiers in Chemistry, 2022)
Objective: To prepare and validate the chemical structure of the cefotaxime dimer and cefotaxime trimer impurities. Methods: A concentrated polymer solution of cefotaxime sodium was obtained using a concentrated solution degradation method. The cefotaxime dimer and trimer impurities were separated and purified by preparative high-performance liquid chromatograph (HPLC), and the pure cefotaxime dimer and trimer were obtained by a freeze-drying method. The two impurities were characterized by infrared (IR) spectroscopy, ultraviolet (UV) spectroscopy, mass spectroscopy, and nuclear magnetic resonance (NMR, including one-dimensional and two-dimensional NMR). The groups corresponding to the characteristic absorption peaks in the UV and IR spectra were analyzed, and the 1H and 13C NMR signals were assigned. Results: The polymerization sites and stereoscopic configuration of the dimer and trimer impurities were validated for the first time. Conclusion: This study is of great significance for the study of the structures and quality control of polymer impurities in cephalosporin drugs.